Effects of externally-applied, non-pharmacological Interventions on short- and long-term symptoms and inflammatory cytokine levels in patients with knee osteoarthritis: a systematic review and network meta-analysis - Wang, Zhen; Xu, Hui; Wang, Zheng; Zhou, Hang; Diao, Jieyao; Zhang, Lijuan; Wang, Yu; Li, Miaoxiu; Zhou, Yunfeng (Frontiers in Immunology, 2023)
Background: With the continuous development of clinical medicine, an increasing number of non-pharmacological interventions have been applied for the treatment of knee osteoarthritis (KOA), with the results of several recent randomized controlled trials (RCTs) showing that a variety of externally-applied, non-pharmacological interventions (EANPI) can improve symptoms and inflammation in patients with KOA. However, the relative benefits and disadvantages of non-drug therapies remain uncertain, and an optimal treatment strategy has not yet been determined.Objective: This study applied network meta-analysis (NMA) to compare and rank the effectiveness of EANPI on the short-and long-term clinical symptoms and inflammatory cytokine levels in patients with KOA. Methods: Two independent researchers searched online databases and performed manual retrieval of related citations to identify RCTs that met the selection criteria for the network meta-analysis. These researchers retrieved studies indexed from database inception to August 2023 and performed data extraction and assessment of the risk of bias. Results: The analysis included 80 RCTs involving 8440 participants and nine externally-applied, non-pharmacological therapies. The treatment courses ranged from 1 to 12 weeks, with follow-up periods ranging from 4 to 24 weeks. The results of the NMA indicated that each non-drug therapy was superior to sham intervention in improving all outcome indicators. Except for the VAS and WOMAC pain outcomes, all non-drug therapies had better efficacy than pharmacological treatments. For short-term VAS and TNF-α, extracorporeal shock wave performed better than other therapies. Radiofrequency therapy may be the most promising method to reduce long-term VAS, short-and long-term WOMAC pain, and IL-1β level. Tuina therapy may be a significant choice for short-and long-term outcomes of WOMAC function and range of motion (ROM).The results of the comprehensive comparison of the outcome indicators in 9 different EANPI indicated that radiofrequency and Tuina therapy were more effective and consistently ranked high in improving clinical symptoms in the short and long term. Radiofrequency is effective at relieving pain, and Tuina therapy can be given priority for treatment when hypofunction is the main symptom. EANPI to improve pain symptoms may be related to the regulation of inflammatory cytokine levels, which may be a potential mechanism of action.